Why Aren't Women Sharī'a Court Judges? The Case of Syria - Cardinal, Monique (Islamic law and society, 2010)
Abstract Women make up 14% of the judiciary in Syria and work at all levels of the ordinary courts, both civil and criminal. However, they do not hold office in the personal status courts, special courts that apply codified religious law. This essay presents all opinions, both majority and minority, that explain the legal and social reasons for the non-appointment of women to the Muslim personal status courts known as sharī'a courts. I discuss how religious texts and classical Islamic legal doctrine are used today to undermine women's judicial power and oppose their appointment to the ordinary courts. If a woman cannot act as a sharī'a court judge, then who can? I attempt to answer this all-important question within the Syrian context. The main source of data is interviews conducted with eighty judges and public prosecutors of Damascus and Aleppo between May 2004 and July 2007.